Reliability and quality assessment of AED-related videos on Douyin and Bilibili: a cross-sectional study from China - Luo, Qiuyue; Deng, Xiaolu; Jiang, Yuanjuan; Hu, Dongyue; Wang, Ping; Chen, Xiaoxiong (Frontiers in Disaster and Emergency Medicine, 2025)
BackgroundSudden cardiac arrest remains a significant medical and societal challenge, claiming millions of lives annually. Early defibrillation is one of the few known interventions that can improve survival rates for cardiac arrest victims. Therefore, increasing bystander awareness of emergency care is crucial. The public predominantly gains first-aid knowledge from platforms such as TikTok and Bilibili, which may vary significantly in terms of the quality and trustworthiness of educational content.ObjectiveThis study aims to evaluate the quality and reliability of the top 150 videos related to the operation of automated external defibrillators (AEDs) on the Douyin and Bilibili video platforms.MethodsOn February 1, 2025, we conducted a search using the keyword “AED operation” on Douyin and Bilibili. We included the first 150 videos that met the inclusion criteria. These videos were classified by content and source. The quality and reliability of the videos were evaluated using the Global Quality Score and the modified DISCERN tool. Furthermore, we examined the relationships between video quality and various factors, including video duration, publication time, and metrics, such as likes, comments, shares, and follower count.ResultsOur analysis revealed considerable variation in the quality of AED-related videos across Douyin and Bilibili. Videos produced by medical institutions or professional medical influencers were more scientifically grounded, practical, and authoritative. Additionally, the study showed that longer videos tended to be of higher quality, and increased video interaction (e.g., likes, comments) helped expand videos' reach, boosting public confidence in emergency care.